System of delay difference equations with continuous time with lag function between two known functions - Hajnalka Péics; Andrea Rožnjik; Valeria Pinter Krekić; Márta Takács (Electronic Journal of Qualitative Theory of Differential Equations, 2016)
The asymptotic behavior of solutions of the system of difference equations with continuous time and lag function between two known real functions is studied. The cases when the lag function is between two linear delay functions, between two power delay functions and between two constant delay functions are observed and illustrated by examples. The asymptotic estimates of solutions of the considered system are obtained.